Digital Literacy, Technological Facility Provision, and Learning Motivation as Determinants of Social Studies Engagement and Society 5.0 Readiness Among Indonesian Madrasah Students - Agung Mustofa; Sulastri Rini Rindrayani; Ria Fajrin Rizqy Ana (SAGA: Journal of Technology and Information System, 2025)
This study examines how the availability of technology-based instructional facilities and students' digital literacy competencies shape Social Studies (Ilmu Pengetahuan Sosial/IPS) learning engagement and preparedness for the Society 5.0 paradigm, while concurrently exploring the moderating and mediating functions of learning motivation within these relationships. A quantitative, cross-sectional survey design was adopted, drawing a stratified proportional random sample of 111 junior secondary students from MTs Darunnajah Trenggalek, Indonesia, for the 2024/2025 academic year. Data collection employed a closed-response Likert instrument comprising 144 items across five theoretical constructs, and analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0 with 5,000 bootstrap resamples. Findings confirm that both technology-based facility provision and digital literacy competency exert statistically significant positive influences on IPS learning engagement and Society 5.0 preparedness. Digital literacy emerged as the strongest direct predictor of student readiness (β = 0.288, p = 0.001), whereas facility availability demonstrated the greatest impact on intrinsic learning motivation (β = 0.412, p < 0.001). Learning motivation functioned as a meaningful moderator across all four predictor-to-outcome pathways and additionally served as a partial mediator between facility provision and student readiness (β = 0.185, T = 3.450, p = 0.001). The composite R² values for the endogenous constructs ranged from 0.585 to 0.658, reflecting adequate model explanatory power. These results collectively underscore that deliberate investment in digital infrastructure and literacy cultivation, reinforced by systematic nurturing of motivational dispositions, constitutes an evidence-based pathway for enhancing the quality and future-readiness of Social Studies education in Indonesian Islamic secondary school contexts.